Materiality, Making and Meaning: Building the Artist Record through Conservation in Indonesia - Eliza O’donnell; Nicole Tse (IJCAS (International Journal of Creative and Arts Studies), 2018)
Ways of knowing and understanding the artistic process are not fixed, and there are multiple perceptions that rely on the experience of the viewer and sources that inform them. this paper presents a case study of a conservation residency and collaborative treatment of indonesian artist Entang wiharso’s ‘landscaping My Brain’ (2001) oil on canvas triptych painting, to examine how we understand the artistic process from a conservation perspective and how this material knowledge contributes to the artist record. an interdisciplinary methodology for the conservation treatment of wiharso’s painting relied on technical and visual examination of the artwork in partnership with artist interviews and archival research. the residency concluded with an exhibition of the painting in an ‘active state of conservation’, highlighting the conservation decisionmaking process as value based and culturally grounded, leading to questions of authority, the role of technical-conservation expertise, what approaches work best, who should do the work and what knowledge informs it. in considering how we understand the artistic process, this paper will draw on the importance of practice-based interdisciplinary learning between conservator, artist, collector, curator and students, and the potential for collaboration and knowledge building at the intersection of these disciplines.